2009
DOI: 10.3748/wjg.15.2170
|View full text |Cite
|
Sign up to set email alerts
|

Emerging clinical and therapeutic applications of Nigella sativa in gastroenterology

Abstract: Nigella sativa (N. sativa ) decreases DNA damage and thereby prevents initiation of carcinogenesis in colonic tissue secondary to exposure to toxic agents such as azoxymethane. N. sativa is of immense therapeutic benefit in diabetic individuals and those with glucose intolerance as it accentuates glucose-induced secretion of insulin besides having a negative impact on glucose absorption from the intestinal mucosa. N. sativa administration protects hepatic tissue from deleterious effects of toxic metals such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…N. sativa is not toxic to normal cells though TQ suppresses proliferation of tumor cells [34]. N. sativa may be of therapeutic benefit in diabetic individuals and those with glucose intolerance as it accentuates glucose-induced secretion of insulin besides having a negative impact on glucose absorption from the intestinal mucosa [35].…”
Section: Review and Discussionmentioning
confidence: 99%
“…N. sativa is not toxic to normal cells though TQ suppresses proliferation of tumor cells [34]. N. sativa may be of therapeutic benefit in diabetic individuals and those with glucose intolerance as it accentuates glucose-induced secretion of insulin besides having a negative impact on glucose absorption from the intestinal mucosa [35].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Results suggested that N. sativa treatment protects the rat liver against hepatic ischemia reperfusion injury [86] . N. sativa administration protects hepatic tissue from deleterious effects of toxic metals such as lead, and attenuates hepatic lipid peroxidation following exposure to chemicals such as carbon tetrachloride [52] . Cadmium (Cd ++ ) causes alteration of the cellular homeostasis and oxidative damage.…”
Section: Hepato-protective Activitymentioning
confidence: 99%
“…N. sativa oil has a significant activity in diabetic and dyslipidemic patients [51] . N. sativa is of immense therapeutic benefit in diabetic individuals and those with glucose intolerance as it accentuates glucose-induced secretion of insulin besides having a negative impact on glucose absorption from the intestinal mucosa [52] . The effects of the TQ in STZ-induced diabetes in rats were investigated.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…It was reported that, thymoquinone(TQ) has many medicinal properties like; anti-oxidant (Meral et al, 2001;Shalaby and khater, 2007;Zegarac et al, 2009 ), anti-inflammatory (Hajhashemi et al, 2004), anti-tumor (Banerjee et al, 2010), analgesic and other properties (Kaleem et al, 2006;Bhatti et al, 2009). On the other side, Kapoor ( 2009) proved that TQ protects hepatic tissue from deleterious effects of toxic metals such as lead, and attenuates hepatic lipid peroxidation following exposure to chemicals such as carbon tetrachloride. However, in spite of the large number of the antioxidant and hepatoprotective studies carried out worldwide on N. sativa oil and TQ, scrutiny of published articles (Al-Ghamdi, 2003) showed that there is a need to investigate the .…”
Section: Introductionmentioning
confidence: 99%